Inquiring children and elementary school teachers to diagnose their conceptions about islands - Vasconcelos, Clara; Paz, Marta (Frontiers in Education, 2023)
Current challenges faced by modern societies assign larger importance to geological knowledge, particularly in the youngest, as geoscience education is an important path toward a more comprehensive understanding of the Earth’s processes and, therefore, to achieve a more sustainable world. The present investigation aims to deepen the knowledge regarding the conceptions related to islands and island formation. Children’s diagrams and drawings are prototypical representations of how they view and understand their world and can also illustrate misunderstandings in their knowledge. This study focuses on the conceptions of islands in elementary school children (K-9) and elementary school teachers. For that purpose, the investigation resorted to a small survey based on a drawing task. The sample consisted of 118 elementary school students (n = 118), whose ages ranged from 6 to 10 years, and their four elementary school teachers (n = 4), whose ages ranged from 43 to 49 years. In line with prior studies that acknowledged the existence of many misconceptions regarding geology topics, this investigation found unscientific ideas about islands, both in students and teachers. The study results also show that students and teachers share misconceptions about the formation of islands and their relation with the seafloor. The implications of our findings for science education are discussed, namely, the development of an Earth sciences education for elementary schooling and the construction of educational resources better adapted to the teaching and learning of the topic.